Quality of care in the oncology outpatient setting from patients' perspective: a systematic review of questionnaires' content and psychometric performance. Issue 4 (5th September 2014) - Brédart, A.; Kop, J.‐L.; Efficace, F.; Beaudeau, A.; Brito, T.; Dolbeault, S.; Aaronson, N.; for the EORTC Quality of Life Group
Abstract Background Cancer care is increasingly provided in the outpatient setting, requiring specific monitoring of care quality. The patients' perspective is an important indicator of care quality and needs to be assessed with well designed, psychometrically sound questionnaires. We performed a systematic literature review of currently available patient satisfaction measures for use in cancer outpatient care settings. Methods We carried out MEDLINE/PubMed, PsycINFO, CINAHL, and Scopus searches of papers published over the past 15 years that describe cancer patient satisfaction questionnaires for use in the outpatient setting. We used the adapted COSMIN checklist to assess the quality of the questionnaires' measurement properties. Results A total of 6677 citations were identified and 76 relevant articles were read, of which 55 were found either not to be relevant or to provide insufficient psychometric information. The remaining 21 studies pertained to 14 patient satisfaction questionnaires. Continuity and transition, accessibility, and involvement of family/friends were less frequently addressed despite their relevance in outpatient oncology. Almost half of the psychometric studies did not provide information on item level missing data. Most internal consistency estimates (Cronbach's α) were satisfactory. Few studies reported test–retest assessment (n = 5), used confirmatory factor analysis (n = 2), or assessed fit to a graded response item response theory model (n = 3). Only three questionnaires were cross‐culturally validated. Conclusion Important aspects of care may be missed by current patient satisfaction questionnaires for use in the cancer outpatient setting. Additional evidence is needed of their psychometric performance, especially for cross‐cultural comparative assessments. Copyright © 2014 John Wiley & Sons, Ltd.